Structure and Function of CC-Chemokine Receptor 5 Homologues Derived from Representative Primate Species and Subspecies of the Taxonomic Suborders Prosimii and Anthropoidea - Kunstman, Kevin J. (American Society for Microbiology, 2003)
A chemokine receptor from the seven-transmembrane-domain G-protein-coupled receptor superfamily is an essential coreceptor for the cellular entry of human immunodeficiency virus type 1 (HIV-1) and simian immunodeficiency virus (SIV) strains. To investigate nonhuman primate CC-chemokine receptor 5 (CCR5) homologue structure and function, we amplified CCR5 DNA sequences from peripheral blood cells obtained from 24 representative species and subspecies of the primate suborders Prosimii (family Lemuridae) and Anthropoidea (families Cebidae, Callitrichidae, Cercopithecidae, Hylobatidae, and Pongidae) by PCR with primers flanking the coding region of the gene. Full-length CCR5 was inserted into pCDNA3.1, and multiple clones were sequenced to permit discrimination of both alleles. Compared to the human CCR5 sequence, the CCR5 sequences of the Lemuridae, Cebidae, and Cercopithecidae shared 87, 91 to 92, and 96 to 99% amino acid sequence homology, respectively. Amino acid substitutions tended to cluster in the amino and carboxy termini, the first transmembrane domain, and the second extracellular loop, with a pattern of species-specific changes that characterized CCR5 homologues from primates within a given family. At variance with humans, all primate species examined from the suborder Anthropoidea had amino acid substitutions at positions 13 (N to D) and 129 (V to I); the former change is critical for CD4-independent binding of SIV to CCR5. Within the Cebidae, Cercopithecidae, and Pongidae (including humans), CCR5 nucleotide similarities were 95.2 to 97.4, 98.0 to 99.5, and 98.3 to 99.3%, respectively. Despite this low genetic diversity, the phylogeny of the selected primate CCR5 homologue sequences agrees with present primate systematics, apart from some intermingling of species of the Cebidae and Cercopithecidae. Constructed HOS.CD4 cell lines expressing the entire CCR5 homologue protein from each of the Anthropoidea species and subspecies were tested for their ability to support HIV-1 and SIV entry and membrane fusion. Other than that of Cercopithecus pygerythrus, all CCR5 homologues tested were able to support both SIV and HIV-1 entry. Our results suggest that the shared structure and function of primate CCR5 homologue proteins would not impede the movement of primate immunodeficiency viruses between species.